2021
DOI: 10.1097/gme.0000000000001811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral versus transdermal estradiol plus micronized progesterone on thyroid hormones, hepatic proteins, lipids, and quality of life in menopausal women with hypothyroidism: a clinical trial

Abstract: Objective: The aim of the study was to evaluate the effects of usual doses of oral estradiol with transdermal estradiol and the effects of these estrogens plus micronized progesterone (MP) in menopausal women with primary hypothyroidism. Methods: Twenty women were randomized to 12 weeks of treatment with estradiol 1 mg tablets or estradiol 1 mg gel. Then, women with a uterus received a 100 mg capsule of oral MP. Thyroid function, thyroxine-binding globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…plasma free T3 concentration was found to be higher coincident to a greater leucine oxidation rate in the ML versus EF phase in one study (Lariviere et al 1994). P4 binds PR within the thyroid gland to promote T3/thyroxine (T4) secretion and reduce its binding to the plasma protein, thyroid-binding globulin to maximise free T3 availability (Torre et al 2020;Kaminski et al 2021) thereby accounting for the higher resting metabolic rate (Benton et al 2020) and thus possibly protein catabolism reported in the luteal phase compared with follicular phase.…”
Section: Mechanisms Behind Menstrual Cycle Effects On Protein Metabolismmentioning
confidence: 99%
“…plasma free T3 concentration was found to be higher coincident to a greater leucine oxidation rate in the ML versus EF phase in one study (Lariviere et al 1994). P4 binds PR within the thyroid gland to promote T3/thyroxine (T4) secretion and reduce its binding to the plasma protein, thyroid-binding globulin to maximise free T3 availability (Torre et al 2020;Kaminski et al 2021) thereby accounting for the higher resting metabolic rate (Benton et al 2020) and thus possibly protein catabolism reported in the luteal phase compared with follicular phase.…”
Section: Mechanisms Behind Menstrual Cycle Effects On Protein Metabolismmentioning
confidence: 99%
“…It modulates the synthesis of TSH in the pituitary gland [24,25]. Estrogen can also impact the levels of thyroid-binding proteins in the bloodstream, which, in turn, affects the transport and availability of thyroid hormones for cellular uptake and metabolism [26]. Moreover, elevated estrogen levels have been positively associated with developing autoimmune thyroid disorders, such as Hashimoto's thyroiditis [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact of female sex hormones on substrate utilization, estrogen and progesterone also impact resting energy expenditure. Recent works demonstrate estrogen can increase the pituitary gland to secrete key hormones that regulate the metabolic rate, such as thyroid hormones and growth hormone [42,43]. At rest, EUM females exhibit heightened fat oxidation, as indicated by a decreased respiratory exchange ratio, and a 2.5-11.5% higher resting energy expenditure during the LP of the menstrual cycle when ovarian hormones peak [44,45].…”
Section: Resting Energy Expenditure and Female Sex Hormonesmentioning
confidence: 99%